Supply Chain Finance Information Model in Thailand - Artaphon Chansamut (ExcelingTech, 2023)
The paper aim to develop and to evaluate supply chain finance information model in Thailand. The sample consisted of ten experts who have more than six years’ experience in supply chain and Information and were selected by purposive sampling. After analysing the data, it showed that supply chain finance information model in Thailand comprises four main components, namely buyer, supplier and lender. The data analysed by using arithmetic mean and standard supply chain finance information model in Thailand After analysing the data, it showed that supply chain finance information model in Thailand is high level of appropriateness, suggesting that supply chain finance information model in Thailand able to develop information .